PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN TANJUNG JABUNG TIMUR - Abdul Rahim; Saiyid Syech; Muhammad Zahari MS (J-MAS (Jurnal Manajemen dan Sains), 2017)
The purpose of this research is to gain an overview of the working environment, competence, motivation and work performance of the employee at Tanjung Jabung District Education Office; and to know the influence of the working environment andwork motivation against the competencies and performance of pergawai; as well as to know the influence of work motivation on performance. To answer the research objectives, the author uses the theory that studies related to the variable of researchi.e. working environment theory, competence, motivation and work performance. In addition the author also searched for relevant earlier research in the form of articles/journals and previous thesis to support this research. The population in this research is an employee at Tanjung Jabung District Education Office East of 65 employees.Due to the number of population in this study less than 100 people then in this research sampling method using the method of census. Analysis techniques using pathanalysis to see the direct and indirect influence, and was succeeded by testing the RSquare and hypothesis testing partially and simultaneous with t-test and F-test of the test path analysis is done, the results the research showed that the work environment has an impact on the competence and motivation of working and performance of employees. Where on the basis of the results of the test t (partial) and F (Simultaneous) indicate that the work environment and competence has a significant and positive influence towards the working motivation and performance, as well as the motivation of working also has the influence of the significant and positive towards the performance of employees. This explains that if an organization has a good working environment and supported by employees who have good competence, then it would have an effect on the motivation of work that have implications for improved performance against employees on Tanjung Jabung District Education Office. This research makes some conclusions based on results of research i.e. work environment,competence, motivation and performance of employees at Tanjung Jabung DistrictEducation Office in a pretty good condition; the work environment and the competence of a positive and significant effect against the motivation of working either partially or simultaneously; the work environment and the competence of a positive and significant effect on performance clerk either partially or simultaneously; the motivation of working effect on employee performance; and the work environment and competence together through motivation affect direct and indirect employee performance against at Tanjung Jabung District Education Office.Keywords: work environment, competence, Motivation and Work performance.